STUDY ON THE INFLUENCE OF COAL PROPERTIES ON THE LOAD CHARACTERISTICS AND FRACTAL ANALYSIS - HAO ZhiYong; WANG ShuaiLing; CHEN ZhiQiang; MAO Jun (Jixie qiangdu)
In order to study the effect of coal properties on the plow planing cutter load characteristics in the process of coal plough testing by using the self-developed real-time sensor for testing on two planes load properties of coal or rock under,through the wireless acquisition module to collect the test data,get the planer load data curve and carries on the analysis and research on the fractal characteristics of the wavelet. The results show that with the increase of hardness of coal rock,planing force increases gradually,the plough vertical planer X direction,the maximum value of the curve is 35. 642 kN,in the Y direction perpendicular to coal wall,just contact the coal wall produces an instantaneous pulse,reached the minimum value of-19. 831 kN in this curve,in the Z direction along the planer operation,the maximum value is 20. 419 kN; the fractal dimension of load was about1. 5. The fractal dimension in three directions with a coal nature difference,coal load curve fluctuation with lower hardness is more obvious,to reduce the consumption of coal plow cutting coal seam in the process of energy,the smaller the shape factor is better. The results for the properties of coal and rock identification provide a new point of view,to provide data support for the design and optimization of coal plough parts.